PENGARUH PROMOSI, E-WORD OF MOUTH, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BITTERSWEET BY NAJLA (STUDI KASUS DIWILAYAH KOTA TANGERANG) - Lulu Khalda Nur Fadilah; Dihin Septyanto (CV. ADIBA AISHA AMIRA, 2023)
This study aims to find out the Effect of Promotion, E – Word Of Mouth, Product Quality, On Bittersweet by Najla Purchasing Decision (Case Study in Tangerang City Area). The population in this study is all consumers who have bought Bittersweet by Najla and are in Tangerang City. The method of sampling through non-probability sampling techniques obtained samples as many as 100 respondents. The statistical tool used is multiple linear regression analysis. Data processing using SPSS statistics 25.0 software. The results of this study showed that Promotion, E – Word Of Mouth, and Product Quality simultaneously positively influenced the Purchase Decision on Bittersweet by Najla. E – Word Of Mouth, Product Quality has a partial positive effect on Purchasing Decisions. While the Promotion has no effect on the Purchase Decision. To improve the Purchasing Decision on Bittersweet by Najla, it should pay more attention to what consumers want so that consumers will be more interested in buying.